2007
DOI: 10.1002/mus.20768
|View full text |Cite
|
Sign up to set email alerts
|

Glia cells in amyotrophic lateral sclerosis: New clues to understanding an old disease?

Abstract: In classic neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS), the pathogenic concept of a cell-autonomous disease of motor neurons has been challenged increasingly in recent years. Macro- and microglial cells have come to the forefront for their role in multistep degenerative processes in ALS and respective disease models. The activation of astroglial and microglial cells occurs early in the pathogenesis of the disease and seems to greatly influence disease onset and promotion. The role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 153 publications
1
57
0
4
Order By: Relevance
“…These mice failed to display any signs of motor neuron degeneration over a span of 1.5 years. 84 Lino and colleagues 69 attained similar results using a neuron-specific Thy-1 promoter to constitutively express high levels of SOD1 G93A or SOD1 G85R in murine models, confirming that the isolated expression of mSOD1 in motor neurons is insufficient to initiate motor neuron toxicity. Gurney 45 assessed whether the selective enhancement of mSOD1 expression in motor neurons would alter the onset or progression of symptoms in ALS murine models.…”
Section: Contributions Of the Neuronal Microenvironmentmentioning
confidence: 79%
See 3 more Smart Citations
“…These mice failed to display any signs of motor neuron degeneration over a span of 1.5 years. 84 Lino and colleagues 69 attained similar results using a neuron-specific Thy-1 promoter to constitutively express high levels of SOD1 G93A or SOD1 G85R in murine models, confirming that the isolated expression of mSOD1 in motor neurons is insufficient to initiate motor neuron toxicity. Gurney 45 assessed whether the selective enhancement of mSOD1 expression in motor neurons would alter the onset or progression of symptoms in ALS murine models.…”
Section: Contributions Of the Neuronal Microenvironmentmentioning
confidence: 79%
“…45 The inability to reach a threshold effect for mSOD1 expression cannot be excluded as an explanation for the inability to recapitulate disease symptomatology in these murine models. 84 Although the above findings indicate that dysfunction localized to neurons is insufficient to result in motor neuron death, other data have indicated that the involvement of surrounding cells, notably astrocytes and microglia, are required for disease progression. Clement and colleagues 25 engineered 65 murine chimeras composed of wild-type cells and those that expressed levels of mSOD1 protein necessary to induce motor neuron cell death.…”
Section: Contributions Of the Neuronal Microenvironmentmentioning
confidence: 96%
See 2 more Smart Citations
“…SOD inclusion formation may recruit proapoptotic BAX to mitochondria. A possible non-cell autonomous process characterized in ALS is inflammation, which appears in microglial and astroglial cells, resulting in mitochondrial damage and apoptosis [34][35][36]. Protein misfolding and aggregation mechanisms are still unclear, but protein inclusions have been found in human ALS, including ubiquitinated skein-like inclusion, bunina bodies, and hyaline inclusions rich in neurofilament proteins [37].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%